2017
DOI: 10.26444/aaem/74716
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hepatitis B Surface Antigen Titers two decades after vaccination in a cohort of students and post-graduates of the Medical School at the University of Palermo, Italy

Abstract: Introduction and objective. The introduction of a vaccine against hepatitis B virus (HBV) for newborn babies in Italy in 1991, extended to 12-year-old children for the first 12 years of application, has been a major achievement in terms of the prevention of HBV infection. The objective of this study was to analyse the long-term immunogenicity and effectiveness of HBV vaccination among healthcare students with different working seniorities. Materials and method. A cross-sectional observational study of undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…The correlation between the immunization status and the number of doses administrated confirms the usefulness of booster doses of the vaccine in uncovered sub-took <3 doses) or in administering the doses (the site and method of administration) may be a possible explanation for the reduced vaccination coverage in some subjects. In the studied population, the students who received the vaccine within the first year of age were less effectively covered, compared to those who received it later, confirming the results of another study [8], while being in contrast to the WHO recommendations that stress the importance of vaccinating infants at birth to prevent students. In this context, occupational physicians should improve the vaccination rates by limiting the number of non-immunized subjects in their professional group, in order to increase the actual safety of healthcare workers, in particular medical students.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The correlation between the immunization status and the number of doses administrated confirms the usefulness of booster doses of the vaccine in uncovered sub-took <3 doses) or in administering the doses (the site and method of administration) may be a possible explanation for the reduced vaccination coverage in some subjects. In the studied population, the students who received the vaccine within the first year of age were less effectively covered, compared to those who received it later, confirming the results of another study [8], while being in contrast to the WHO recommendations that stress the importance of vaccinating infants at birth to prevent students. In this context, occupational physicians should improve the vaccination rates by limiting the number of non-immunized subjects in their professional group, in order to increase the actual safety of healthcare workers, in particular medical students.…”
Section: Resultssupporting
confidence: 83%
“…The serological reference values of the total HBsAb were the international values used by the WHO standard criteria. For the purposes of the study, students with HBsAb ≥10 mIU/ml were considered protected against hepatitis B, a value also considered in other Italian and international studies [4][5][6][7][8].…”
mentioning
confidence: 99%
“…This study concluded that HBV vaccination at age of 12 years was significantly associated with having protective anti‐HBs. In particular, a protective anti‐HBs titre was about fourfold more frequent among subjects vaccinated during adolescence than those vaccinated at infancy . In a similar study, 2 groups of students attending the University of Padova Medical School were enroled between 2004 and 2011 and HBV antibodies and antigens were measured.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, a protective anti-HBs titre was about fourfold more frequent among subjects vaccinated during adolescence than those vaccinated at infancy. 48 In a similar study, 2 groups of students attending the University of Padova Medical School were enroled be- Our recommendation is to include the screening model described in the routine assessment of biological risk of medical students and healthcare professionals. One of the most prominent research questions in future studies is to understand what the most effective formulation of booster vaccine doses is to achieve seroconversion in seronegative subjects yet immunized, and also evaluate the adverse effects.…”
Section: Ta B L E 1 Analysis Of Determinants Of Seroconversion After mentioning
confidence: 99%
“…Despite declining serum levels of antibody, international evidence shows that vaccine-induced immunity continues to prevent clinical disease or detectable viremic HBV infection. 30 So, it would seem that administering the vaccine at 12 years of age induces a better immune system response. Such a better response could suggest the usefulness of administering, in addition to compulsory vaccination at birth, a dose booster in professionally exposed persons.…”
Section: Discussionmentioning
confidence: 99%